Central venous disease in hemodialysis patients - Hoon Suk Park; Joonsung Choi; Jun Hyun Baik (The Korean Society of Nephrology, 2019)
Central venous disease (CVD) is difficult to treat and often resistant to treatment. In CVD, hemodialysis vascular access should sometimes be abandoned, or in serious cases, the patient's life may be threatened. Therefore, prevention is ideal. However, as the prevalence of chronic kidney disease (CKD) has increased steadily with population aging, CKD patients with a peripherally inserted central catheter (PICC) are encountered frequently. PICCs can cause CVD, and the basilic vein, which is regarded as the important last option for native arteriovenous fistula (AVF) creation in end-stage renal disease (ESRD) patients, is destroyed frequently after its use as the entry site of PICC. The most well-established risk factors for CVD are a history of central venous catheter (CVC) insertion and its duration of use. Therefore, to reduce the incidence of CVD, catheterization in the central vein (CV) should be minimized, along with its duration of use. In this review, we will first explain the basic territories of the CV and introduce its pathophysiology, clinical features, and advanced treatment options. Finally, we will emphasize prevention of CVD.